Drug Susceptibility Profile of Mycobacterium tuberculosis Isolated from Patients Visiting National Tuberculosis Centre, Nepal - Dahal, S.; Banjara, M.R.; Khadka, D.; Ghimire, G.; Sharma, S. (Tribhuvan University Journal of Microbiology, 2018)
Objectives: The objective of this study was to assess drug susceptibility pattern of Mycobacterium tuberculosis (MTB). Methods: This cross-sectional study was carried out among 145 clinically suspected and previously treated pulmonary tuberculosis patients visiting National Tuberculosis Centre, Bhaktapur, Nepal. After obtaining written informed consent, questionnaire was administered and sputum samples were collected from each patient. Each sample was subjected to Ziehl-Neelsen (ZN) staining and cultured on Lowenstein Jensen (LJ) medium at 37ºC for 8 weeks. MTB isolates were identified by growth rate and colony morphology, confirmed by biochemical tests and drug susceptibility testing (DST) of identified isolates was performed by proportion method. Results: A total of 49.7% (n=72) sputum samples were positive for MTB by culture and 46.9% (n=68) were positive by ZN staining. Among culture positive isolates of MTB (n= 72), 25% (n=18) were resistant to at least one drug. The prevalence of multi drug resistant tuberculosis (MDR-TB) was 15.3% (n=11) of which 5.56% (n=4) were resistant to rifampicin (RIF) only, 1.39% (n= 1) were resistant to isoniazid (INH) only. Out of 18 resistant isolates, 61.1% (n=11) were resistant to both RIF and INH, 21.43% (n=3) resistant to INH were susceptible to RIF and 26.67% (n=4) resistant to RIF were susceptible to INH. Smoking (P=0.001) and coughing (P=0.009) were statistically significant with isolation of MTB. Conclusion: Since the prevalence of MDR-TB was high, MDR-TB strains should be identified in order to initiate second line treatment.